MRI OF BRACHIAL PLEXUS INJURY COMPARED WITH INTRAOPERATIVE FINDINGS - SANMAHACHATI, Sukhonta; MAIRAING, Eimorn; SRINAKARIN, Jiraporn; VIPULAKORN, Kittiwan; JIRARATTANAPOCHAP, Kitti; BOONPONGSATHIAN, Wuttisak (The ASEAN Journal of Radiology, 2023)
Brachial plexus MRI of 11 patients who had both clinical and intraoperative findings of traumatic brachial plexus injury (BPI) in Srinagarind Hospital KKU during June 1997 — January 1998 were reviewed. The sensitivity of MRI for BPI compared with intraoperative findings was 88.88%, 9.09% false positive and 9.09% as false negative or doubtful result. Particularly on T2W images, we could document the lesions as a high signal intensity of CSF around the affected nerve roots. The increased signal intensity of the nerve tissue and muscles are due to oedema, distortion of the nerves, hematoma and posttraumatic neuroma. 8/11 (72.7%) had preganglionic rootlet avulsion, with 61.29% associated pseudomeningocoele, predominantly C7,8 root involvement. One from this group was considered as false positive result. One case had only neural contusion and other two cases were documented as perineural fibrosis intraoperation. Abbreviation: BPI = Brachial Plexus Injury.